Factors Associated With Pregnancy Outcomes After Intrauterine Insemination - Batara Imanuel Sirait; Frisca Angreni; Indira Naomi Hutahaean (International Journal of Health Engineering and Technology, 2026)
Infertility is a reproductive disorder defined as the inability to achieve a clinical pregnancy after 12 months or more of regular unprotected intercourse. It may be caused by female and/or male factors. Intrauterine insemination (IUI) is a form of assisted reproduction commonly used to treat subfertility. In Indonesia, infertility affects an estimated 10–15% of couples, equivalent to 4–6 million out of 29.8 million couples of reproductive age. This study aimed to evaluate factors associated with pregnancy success following IUI at Morula IVF Clinic, Jakarta, during January - December 2023. An analytic descriptive design was applied, and associations were tested using the Chi-square method. A total of 199 patients were included, with an overall IUI pregnancy success rate of 8.5%. Successful pregnancies were most frequently observed among wives aged 25 - 35 years, those with a body mass index of 18.5–24.9 kg/m², and cycles with pre-wash semen volume of 2 - 5 mL, sperm concentration >16 million, and sperm motility >30%. Chi-square analysis demonstrated that only sperm motility was significantly associated with IUI success (p=0.029), while wife’s age, body mass index, pre-wash semen volume, and sperm concentration showed no significant association.